How to identify national dimensions of poverty? The constitutional approach - Francesco Burchi; Pasquale De Muro; Eszter Kollar (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
With the signing of the 2030 Agenda, the international community has committed to ending poverty in all its forms. This first Sustainable Development Goal (SDG) recognises poverty as a multidimensional phenomenon that goes beyond the simple lack of a sufficient amount of income. However, the way the SDG 1 and, in particular, Target 1.2 – “reduce ?…? poverty in all its dimensions according to national definitions” – are formulated poses challenges for its operationalisation. Which specific dimensions of poverty should a country focus on? How can we identify them? Is it possible to agree on a universal set of dimensions with which to compare poverty across several countries? Recently, significant advancements have been made in the measurement of multidimensional poverty; however, how dimensions of poverty are selected is often overlooked. Empirical studies have employed different approaches, ranging from a data-driven approach to the use of participatory methods or surveys to detect context-based dimensions. This Briefing Paper discusses the pros and cons of the existing approaches and argues in favour of a new one, called the Constitutional Approach. The central idea is that the constitution of a democratic country, together with its official interpretations, can be a valid source of ethically sound poverty dimensions. What is the value added of the Constitutional Approach? And what are the policy implications of adopting it? The approach is grounded on a clear understanding of what poverty is, rather than an ad hoc approximation of it based on data availability. Only with a clear definition can poverty be measured, and anti-poverty strategies adequately designed and implemented. By drawing on norm-governed national institutions that have shaped societal attitudes, the resulting list of dimensions is more legitimate and likely to be accepted and used by national policy-makers and endorsed by the public. The selecting of valuable societal dimensions is not just a technocratic issue but must be grounded in shared ethical values. The approach does not require the collection of additional information to understand which poverty dimension should be prioritised. However, one must consider that this approach is only suitable for democratic countries, whose constitutions: are the result of a broad-based participatory process, still enjoy wide consensus and recognise at least the principle of equality among all citizens. To compare multidimensional poverty at the global level, the approach could be extended by examining a core list of overlapping dimensions across several countries. Given the above strengths, the German Federal Ministry for Economic Cooperation and Development (BMZ), which has a vital role in the Multidimensional Poverty Peer Network, could recommend this approach to governments to track country progress in SDG 1.
Keywords: 330; Armut und Ungleichheit; Agenda 2030